A Frightening Public Space: The Social Phenomenon of Motorcycle Gangs on the Highways of Makassar City 2014 - Ahmadin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Crime in urban areas is a social phenomenon that is sometimes very disturbing to society, so that it is sometimes imagined as a terrible space of horror for many people. A reality like this has happened on the highway of Makassar, a city in Indonesia located in the province of South Sulawesi. This criminal practice was carried out by a group of motorbike riders at night. This research examines several factors that cause crime and possible solutions, so that it does not have a negative impact on public peace and damage the city's image. This research method is descriptive using qualitative data. The results of the research show that the emergence of the phenomenon of motorized crime committed by teenagers is partly triggered by a lack of control from both parents and city security guards. As a result, criminal practices occur which cause road users to become victims.